Influência da irradiação a laser infravermelho de baixa potência em neutrófilos de camundongos infectados com Paracoccidioides brasiliensis - Bani, Giulia Maria De Alencar Castro (2015)
Paracoccidioides brasiliensis (Pb) is the etiologic agent of Paracoccidioidomycosis (PCM), an endemic systemic mycosis most prevalent in Latin America and Brazil. Through the study of experimental model, it was possible to make a comparison and classify different strains of inbred mice infected with Pb as resistant or susceptible and the understanding the mechanisms of immune response involved in the disease. Once infected, the host immune system has several mechanisms both the innate to adaptive immunity to contain the infection. Phagocytes, such as macrophages and polymorphonuclear neutrophils (PMN) play a central role in the immune response against the fungus. Besides being the link between innate and acquired immunity, the PMN are effective in host defense against Pb because are restricted to the site of injury caused by fungus. In this perspective, therapy using Low Level Light Therapy (LLLT) with infrared laser in vivo emerges as a method to stimulate the activity stimulated by immune cells such as PMN, without changing its function, to be described as a method of modulating immune cells. LLLt was applied ate two points of paw hind mouse, a power of 50 mW and a wavelength of 780nm, mice infected with Pb18 or inoculated with Zymosan by method air pouch. On irradiated and non-irradiated animals, we assessed the effect of LLLT in vivo production of total protein production capacity of reactive oxygen species (ERO) and freshly isolated PMN fungicidal capacity of the site of infection. The results showed that the active LLLT PMNs, for groups of irradiated mice regardless of the stimulus for inflammation, there was an increase in the production of total proteins, the ability fungicide and ROS production compared with the control group. Although the laser has decreased the total number of PMNs collected from mice infected with Pb18, the viability of the cells in all experimental groups remained highly viable. The results showed that the active LLLT PMNs, resulting in a greater capacity fungicide, suggesting that the laser can be used as adjunctive therapy in the treatment of PCM.